2014
DOI: 10.4314/tjpr.v13i10.7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lipopolysaccharide-induced neuroinflammatory events in Bv-2 microglia by chestnut peel extract

Abstract: Purpose: To evaluate the protective effects of chestnut (Castenea cranata Siebold & Zucc., Fagaceae) peel extract on stimulated BV-2 microglial cells as well as its anti-oxidant properties. Methods: The ethyl acetate fraction of C.cranata peel (CCP) extract was used in the study to evaluate the anti-neuroinflammatory effects in BV-2 microglial cells. Cell viability was performed by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-tetrazolium bromide (MTT) assay. Lipopolysaccharide (LPS) is used to activate BV-2 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…Cerulli and co-workers showed that the pre-treatment of THP1 and THP-1-XBLUE-MD2-CD14 cells with extracts of Castanea sativa shells [ 45 ] or leaves and burs [ 11 ] inhibited both NF-kB activity and NO production after LPS stimulation. The suppression of the excessive NO production and iNOS expression was also reported by Kang [ 46 ] in BV-2 cells pre-treated with chestnut ( Castanea crenata ) peel extracts and stimulated with LPS. Other authors obtained the same results in LPS-stimulated microglia cells treated with isolated flavonoids also found in Castanea , such as kaempferol [ 39 ], isorhamnetin [ 38 ], or astragalin [ 47 ].…”
Section: Discussionsupporting
confidence: 71%
“…Cerulli and co-workers showed that the pre-treatment of THP1 and THP-1-XBLUE-MD2-CD14 cells with extracts of Castanea sativa shells [ 45 ] or leaves and burs [ 11 ] inhibited both NF-kB activity and NO production after LPS stimulation. The suppression of the excessive NO production and iNOS expression was also reported by Kang [ 46 ] in BV-2 cells pre-treated with chestnut ( Castanea crenata ) peel extracts and stimulated with LPS. Other authors obtained the same results in LPS-stimulated microglia cells treated with isolated flavonoids also found in Castanea , such as kaempferol [ 39 ], isorhamnetin [ 38 ], or astragalin [ 47 ].…”
Section: Discussionsupporting
confidence: 71%
“…Lipopolysaccharide (LPS, L2654‐Sigma Aldrich, St. Louis, MO) was used to activate microglia cells. An effective concentration of ‘5 μg/ml’ was selected based on previous studies (Kang, 2014; Kocanci et al, 2024; Xu et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…However, they remain a useful source of bioactive compounds [ 1 , 5 ]. The chestnut inner shell, in particular, has been used for many years in traditional medicine in Asian countries and is known for its antioxidant, antiallergic, antidiabetic, and anti-amnesic properties [ 6 , 7 , 8 , 9 ]. Several studies have demonstrated the biological activities of the Castanea genus, including antioxidant and anticancer activities [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%